PENYULUHAN PENGELOLAAN DAN PEMILAHAN SAMPAH RUMAH TANGGA KEPADA WARGA DESA CIKERUH - Agrivinie Rainy Firohmatillah; Rini Nur Azizah (JURNAL ABDIMAS DOSMA (JAD), 2025)
Cikeruh Village is one of the villages in Jatinagor Subdistrict with the highest population density, generating approximately 6 tons of waste per day, with the largest source being household waste. However, the management and sorting of household waste have not been carried out optimally, causing waste problems to remain a concern. The community service activity, conducted in the form of participatory and educational counseling, directly involved the target group—housewives around Cikeruh Village—using demonstration methods to help them understand. Evaluation through questionnaires showed that 100% of respondents stated that the counseling was beneficial and increased their awareness of the importance of household waste management and sorting, while 94.1% expressed willingness to implement household-scale waste management and sorting practices. This activity also encouraged active participation and commitment from residents in applying household waste management and sorting, as evidenced by their interest in receiving further training on organic waste composting and establishing a waste bank at the village level.